BEYOND THE NORM: PROSTATE CANCER AWARENESS AND SCREENING PRACTICES IN PAKISTANI MEN AGED 40+ WITH AFFECTED FIRST-DEGREE RELATIVES, EMPLOYED AT A PRIVATE ORGANIZATION - Amjad, Tahira; Turab, Asfa; Tameez-ud-din, Sadia; Iftikhar, Fatima; Ashraf, Shoaib; Humayun, Shumaila; Hassan, Ali; Zahra, Tehreem; Jabbar, Arham; Zulfiqar, Ahad; et al. (Journal of Ayub Medical College Abbottabad, 2025)
Background: Prostate cancer is the second most common cancer in men worldwide. In Pakistan, awareness and screening remain limited among high-risk men even with affected first-degree relatives. Evaluating knowledge and behaviours is essential for identifying gaps and improving early detection efforts. Objectives were to assess awareness and screening practices regarding prostate cancer, identify participants with affected first-degree relatives, explore perceived barriers and facilitators, and determine associations between awareness and screening behaviours. Methods: A cross-sectional exploratory study was conducted from May to September 2024 among 156 eligible male employees aged 40 years and above. Ethical approval and informed consent were obtained. Data were collected using a structured questionnaire via Google Forms and analysed using SPSS version 26. Results: Among 156 participants with mean age 49.81±5.61), 125 (80.15%) had inadequate awareness of prostate cancer. Secondary education was completed by 62 (39.74%), and 100 (64.10%) were permanently employed. Information sources included friends or family in 143 (91.7%) and healthcare professionals in 139 (89.1%). Only 5 (3.2%) had first-degree relatives (father) with prostate cancer, and 4 (2.6%) had a positive family history (two uncles and two cousins). Prostate screening was conducted yearly in only 7 (4.5%) participants, while out of 156, 149 (95.5%) never underwent screening due to lack of awareness 100 (64.1%) and expenses 96 (61.5%). Awareness campaigns were recommended by 99 (63.5%) and organizational support by 91 (58.3%). No significant association was found between awareness, education, family history, and screening practices. The questionnaire demonstrated good reliability (Cronbach’s Alpha 0.888). Conclusion: Most men did not have adequate awareness of Prostate Cancer and had low screening practices. Awareness campaigns and organizational support were perceived as the main facilitators.